Strategi Pengembangan SDM pada UMKM Kuliner di Kota Mataram Nusa Tenggara Barat - Hamdi, Subhan; Kartika, Misya; Putra, Danu Pratama; Hifzia, Siti (Journal of Economics and Management, 2024)
This study aims to analyze the strategy of human resource development (HR) in Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Mataram City, West Nusa Tenggara. The main focus of this study is on efforts to improve workforce competence, training management, and adaptation strategies to market and technology dynamics. A qualitative approach is used with data collection techniques in the form of in-depth interviews, observations, and document studies. The results of the study show that effective human resource development involves continuous training, strengthening managerial skills, and the use of digital technology to improve operational efficiency. In addition, collaboration with the government and the private sector is a key factor in increasing the competitiveness of culinary MSMEs in Mataram. This study provides recommendations for stakeholders to integrate human resource development strategies in long-term plans to support sustainable local economic growth.